2009
DOI: 10.1007/bf03182290
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal change in the structure of fig-wasp community and its implication for conservation

Abstract: Figs (Moraceae) and their pollinating wasps (Agaonidae) constitute a famous reciprocal mutualism in which figs provide some female flowers for the development of fig wasp offspring while the fig wasps pollinate fig flowers. However, figs also host many non-pollinating wasps which are either parasitoids or resource competitors of pollinators, and bring no benefit for figs and are detrimental to fig' fitness. Our data on Ficus racemosa in Xishuangbanna showed that the numbers of non-pollinators and the mature sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 30 publications
1
19
0
1
Order By: Relevance
“…Foundress number per syconium also increased with fruit size (N=93, (Figure 4, also see [29]). The quick closure of osiole will prevent the extra more pollinator wasps from entering the syconium cavities and/or from exiting the syconium cavities after pollinators entering lumen, which will create the intensive interference competition among the foundresses in their egg preposition [16]. The experiment here also showed that in the cold season, the ostiole closure will be much slower than that in the warm season after the foundress entering into the syconium cavities.…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations
“…Foundress number per syconium also increased with fruit size (N=93, (Figure 4, also see [29]). The quick closure of osiole will prevent the extra more pollinator wasps from entering the syconium cavities and/or from exiting the syconium cavities after pollinators entering lumen, which will create the intensive interference competition among the foundresses in their egg preposition [16]. The experiment here also showed that in the cold season, the ostiole closure will be much slower than that in the warm season after the foundress entering into the syconium cavities.…”
Section: Resultsmentioning
confidence: 68%
“…Non-pollinators of gall makers in fig/fig wasp mutualism could independently oviposit in the female flowers of F. racemosa and thereby impede both pollinator and viable seed production [23,25,26,40,59,60]. Gall and seed numbers may be greatly affected by non-pollinator oviposition in highly fragmented forests where non-pollinator density is much higher [16,25]. Our experiments in highly fragmented areas showed that viable seed numbers decline with increasing numbers of wasp offspring when we excluded non-pollinators in January but there was no relationship under natural conditions (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Species interactions can also be conspecific density-dependent, such as through competition, or vary with the population density of other species [16,34,35]. This variation can cause large changes in the interaction between species [16].…”
Section: Varying Coefficients Modelsmentioning
confidence: 99%